MED33/447: Moving Medical Curriculum to the World Wide Web: Practical Tips On Using Macromedia Flash Animation in a Case Study on 'Reproductive Physiology' - Kesler, C; Balch, D (JMIR Publications, 1999)
IntroductionThe internet combined with browser-based graphics, animation and streaming media offer a unique opportunity to reach rural students in both synchronous and asynchronous modes, while simultaneously augmenting the resources to students attending class in person. MethodsThis presentation will showcase a semester long course in the undergraduate Nursing curriculum at East Carolina University School of Nursing. The three-hour weekly course utilized streaming media, graphics and animation to educate nursing students. Results: DiscussionAnimations and project management will be broken down into their development components and processes will be explained.